Method for manufacturing metal composite core
By using a combination of high-size magnetic powder with high roundness and low-resistance magnetic force and small-size powder in the metal composite core, combined with an appropriate amount of resin, the problem of reducing core density and magnetic characteristics in the prior art is solved, and the problem of realizing the High density and complex shape core preparation reduces iron loss and heat generation.
Patent Information
- Application Number
- CN201910789211.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-21
- Filing Date
- 2019-08-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2039-08-26
AI Technical Summary
In order to maintain fluidity during the molding process of existing metal composite cores, a large amount of resin is required to be added, resulting in a decrease in the proportion of magnetic powder, a decrease in core density and magnetic characteristics, and it is difficult to prepare cores of complex shapes.
Using composite materials containing large-particle and small-particle magnetic powders, by improving the circularity and magnetic resistance of large-particle powders, combining with an appropriate amount of resin to form a high-density metal composite core, and through specific molding and The hardening process realizes the preparation of cores in complex shapes.
The magnetic characteristics and density of the metal composite core are improved, iron loss is reduced, and cores of various shapes can be effectively prepared, which reduces coil leakage and copper loss and reduces heating.
Smart Images

Figure CN110942882B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composite magnetic material comprising magnetic powder and resin, a metal composite core, a reactor, and a method for manufacturing the metal composite core. Background Art
[0002] Reactors are used in various applications such as office automation (OA) equipment, solar power generation systems, automobiles, uninterruptible power supplies, etc. Reactors are used, for example, in filters that prevent harmonic currents from flowing into output systems, or in voltage step-up and step-down converters that step up and down voltages.
[0003] Reactors are required to have magnetic properties such as magnetic permeability, inductance, and iron loss depending on their use. For example, reactors used in voltage step-up and step-down converters are required to have improved energy conversion efficiency and therefore require small iron loss, which is energy loss.
[0004] In addition, in order to cope with various applications, it is also required to mold the core used in the reactor into an arbitrary shape. As a reactor that responds to such a requirement, there is a reactor including a type of core called a metal composite core. The metal composite core (hereinafter also referred to as MC core) is a core formed by molding a material mixed with metal magnetic powder and resin into a predetermined shape and solidifying it.
[0005] [Prior art literature]
[0006] [Patent Document]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 2012-33727 Summary of the invention
[0008] [Problems to be solved by the invention]
[0009] In the past, the MC core had a material in the form of a slurry, and was formed by pouring the material into a container, so it had the advantage of being easily formed into a desired shape with few restrictions on the shape. On the other hand, in order to improve the fluidity in the container, a certain amount of resin or more needs to be added, so that the proportion of magnetic powder in the material decreases, resulting in a decrease in core density, and as a result, the magnetic properties decrease. In addition, in the MC core, there are other main factors that reduce the magnetic properties in addition to the reduction in core density, and it is expected to suppress these effects and improve the magnetic properties.
[0010] An object of the present invention is to provide a composite magnetic material that is a material for a metal composite core having excellent magnetic properties, a metal composite core, a reactor, and a method for manufacturing the metal composite core.
[0011] [Technical means to solve the problem]
[0012] The inventors and others have conducted intensive research and have obtained the following insights: in a metal composite core using two types of large and small magnetic powders as soft magnetic powders, low magnetic permeability is achieved by increasing the circularity of the first magnetic powder with a larger average particle size and increasing the core density, and low iron loss is achieved by suppressing the coercive force of the first magnetic powder to a low level, and the synergistic effect of these can be used to improve the magnetic properties of the metal composite core.
[0013] In order to achieve the above-mentioned purpose, the present invention is a composite magnetic material obtained by mixing magnetic powder with resin, wherein the magnetic powder comprises a first magnetic powder and a second magnetic powder having an average particle size smaller than that of the first magnetic powder, and the coercive force Hc of the first magnetic powder is less than 0.70 A / cm and the circularity is greater than 0.9.
[0014] The first magnetic powder may have a powder hardness of 278 MPa or more.
[0015] The first magnetic powder may have a coercive force of Hc=0.48 A / cm or less and a circularity of 0.92 or more.
[0016] The first magnetic powder may have a powder hardness of 403 MPa or more.
[0017] The coercive force of the second magnetic powder may be Hc=0.93 A / cm or less and the circularity may be 0.98 or more.
[0018] The second magnetic powder may have a powder hardness of 239 MPa or more.
[0019] The first magnetic powder may be added in an amount of 60 wt % to 80 wt % relative to the magnetic powder, and the second magnetic powder may be added in an amount of 40 wt % to 20 wt % relative to the magnetic powder.
[0020] The mixing amount of the resin may be 3 wt % to 5 wt % of the magnetic powder.
[0021] A metal composite core formed by molding the composite magnetic material is also an embodiment of the present invention.
[0022] The entire surface of the core of the metal composite core of the present invention may be a non-sliding surface.
[0023] A reactor including the metal composite core and a coil is also one embodiment of the present invention.
[0024] In addition, the core manufacturing method of the present invention is a core manufacturing method comprising magnetic powder and resin, wherein the magnetic powder comprises a first magnetic powder having a coercive force Hc=0.70A / cm or less and a circularity of 0.9 or more, and a second magnetic powder having an average particle size smaller than that of the first magnetic powder, and the manufacturing method includes: a mixing step of mixing the magnetic powder with a resin; a molding step of placing the mixture obtained in the mixing step into a prescribed container and molding it; and a hardening step of hardening the resin in the molded body obtained in the molding step.
[0025] [Effects of the Invention]
[0026] According to the present invention, a composite magnetic material that is a material for a metal composite core having excellent magnetic properties, a metal composite core, a reactor, and a method for manufacturing the metal composite core can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a flowchart for explaining the method for manufacturing the reactor according to the embodiment.
[0028] Figure 2 It is a figure for demonstrating a molding process and a pressurizing process.
[0029] Figure 3 The magnetic permeability μ relative to the iron loss Pcv of Examples 1 to 5 and Comparative Example 1 is 12k of charts.
[0030] Figure 4 This is a graph showing the ratio of the apparent density of the MC core to the apparent density of the dust core in Example 4, Example 5, and Comparative Example 1 with respect to the powder hardness of the first magnetic powder.
[0031] Explanation of symbols
[0032] 10: Container
[0033] 20: Composite magnetic materials
[0034] 30, 32: Extruded components
[0035] 40: Coil DETAILED DESCRIPTION
[0036] [1. Implementation Method]
[0037] [1-1. Structure]
[0038] The reactor of this embodiment includes a core and a coil. The core is a metal composite core (hereinafter also referred to as an MC core) composed of magnetic powder and resin. A clay-like mixture mixed with magnetic powder and resin is filled into a specified container and pressurized, thereby the core can be set to a specified shape. The shape of the core can be set to various shapes such as a toroidal core, an I-type core, a U-type core, a θ-type core, an E-type core, an EER-type core, etc.
[0039] As magnetic powder, soft magnetic powder can be used, in particular, Fe powder, Fe-Si alloy powder, Fe-Al alloy powder, Fe-Si-Al alloy powder (sendust), or a mixed powder of two or more of these powders can be used. As Fe-Si alloy powder, for example, Fe-6.5%Si alloy powder and Fe-3.5%Si alloy powder can be used. The average particle size (D50) of the soft magnetic powder is preferably 20μm to 150μm. In this specification, the so-called "average particle size" refers to D50, that is, the median diameter, unless otherwise specified.
[0040] The magnetic powder is composed of magnetic powders with different average particle diameters. That is, the magnetic powder includes a first magnetic powder and a second magnetic powder with an average particle diameter smaller than that of the first magnetic powder. The first magnetic powder and the second magnetic powder ideally have low coercivity. The coercivity of the first magnetic powder is preferably less than 0.70 A / cm, and ideally less than 0.48 A / cm. In an MC core using a magnetic powder with a large coercivity, the hysteresis loop in the MC core also becomes larger. Therefore, the hysteresis loss of the MC core becomes larger. Therefore, by suppressing the coercivity of the first magnetic powder to a low level, a MC core with low iron loss can be achieved. In addition, the coercivity of the second magnetic powder is ideally less than 0.93 A / cm. The reason is that the coercivity of the second magnetic powder has less influence on the hysteresis loop of the MC core than the coercivity of the first magnetic powder. However, if the coercive force of the second magnetic powder exceeds 0.93 A / cm, the hysteresis loop of the MC core also becomes larger, and the hysteresis loss of the MC core becomes larger.
[0041] The first magnetic powder and the second magnetic powder are preferably spherical. The circularity of the first magnetic powder is preferably 0.90 or more, and the circularity of the second magnetic powder is preferably 0.98 or more. The reason is that the gaps between the first magnetic powders become smaller, and more second magnetic powders can easily enter the gaps, which can improve the density and magnetic permeability. When the MC core is pressurized, the pressure applied in the pressurization process is several kg / cm 2 ~tens of kg / cm 2 , and the required number t / cm 2 ~tens of t / cm 2Compared with the powder core (hereinafter also referred to as the powder core), the size is very small, about one thousandth, so the circularity of the magnetic powder can be maintained. That is, in the case of a powder core that needs to be pressed at a high pressure, the circularity of the magnetic powder cannot be obtained.
[0042] In addition, the amount of the first magnetic powder added to the magnetic powder is preferably 60 wt% to 80 wt%. That is, when the magnetic powder is composed of the first magnetic powder and the second magnetic powder, the weight ratio is preferably set to 80:20 to 60:40 for the first magnetic powder: the second magnetic powder. By setting it in the above range, the density of the core can be increased and the iron loss Pcv can be reduced.
[0043] The average particle size of the first magnetic powder is preferably 50 μm to 200 μm. In addition, the second magnetic powder is preferably 3 μm to 25 μm. This is because the second magnetic powder having a small average particle size enters the gaps between the first magnetic powders, thereby increasing the density of the core and reducing the iron loss.
[0044] The powder hardness of the first magnetic powder is preferably 278 MPa or more, and more preferably 403 MPa or more. Unlike the pressed powder core, the MC core uses resin to bond the magnetic powders to each other. In contrast, the pressed powder core deforms the magnetic powder by applying a high pressure in the pressurization process, thereby improving the moldability. In the pressed powder core, the powder hardness is preferably below a certain value, but there is no such restriction in the MC core. In addition, in the case of the MC core, unlike the pressed powder core, the magnetic powder will not be deformed by pressurization, so there will be no adverse effect on the hysteresis loss. In addition, if the first magnetic powder is set to a spherical shape, there is a tendency for the powder hardness to increase. By setting the first magnetic powder to a spherical shape, the magnetic permeability of the MC core can be suppressed to a low level and the density can be increased. In addition, the powder hardness of the second magnetic powder is preferably 239 MPa or more. As with the first magnetic powder, by having a high powder hardness, the density and magnetic permeability of the MC core can be improved.
[0045] In addition, as long as the second magnetic powder having a smaller average particle diameter is included relative to the first magnetic powder having the largest average particle diameter, the second magnetic powder may also include magnetic powders having different average particle diameters. That is, the second magnetic powder may be a magnetic powder whose average particle diameter can be specified as one, or a magnetic powder whose average particle diameter can be specified as two or more. In addition, the materials, i.e., the types, of the first magnetic powder and the second magnetic powder may be the same or different. In different cases, the materials may be three or more. In the case where the magnetic powder is composed of three or more powders, the average particle diameters may also be different in each powder.
[0046] As the first magnetic powder, Fe-based amorphous pulverized powder, powder produced by water atomization, gas atomization, or water-gas atomization can be used. Powder produced by water atomization is particularly preferred. The reason is that water atomization is quenched during atomization, so the powder is difficult to crystallize. The second magnetic powder can be powder produced by water atomization, gas atomization, or water-gas atomization.
[0047] The resin is mixed with the magnetic powder and the magnetic powder is held. When the magnetic powder is composed of powders with different average particle diameters, each powder is held in a homogeneously mixed state. As the resin, a thermosetting resin, an ultraviolet curing resin, or a thermoplastic resin can be used. As the thermosetting resin, a phenol resin, an epoxy resin, an unsaturated polyester resin, a polyurethane, a diallyl phthalate resin, a silicone resin, etc. can be used. As the ultraviolet curing resin, a urethane acrylate resin, an epoxy acrylate resin, an acrylate resin, and an epoxy resin can be used. As the thermoplastic resin, a resin with excellent heat resistance such as a polyimide or a fluororesin is preferably used. The epoxy resin that is cured by adding a curing agent can adjust its viscosity by the amount of curing agent added, etc., and is therefore suitable for the present invention. A thermoplastic acrylic resin or a silicone resin can also be used.
[0048] The resin is preferably contained in an amount of 3 wt% to 5 wt% relative to the magnetic powder. If the content of the resin is less than 3 wt%, the bonding force of the magnetic powder is insufficient and the mechanical strength of the core is reduced. In addition, if the content of the resin is more than 5 wt%, the formed resin enters between the first magnetic powders, and the second magnetic powder cannot fill the gaps, etc. For the above reasons, the density of the core is reduced and the magnetic permeability is reduced.
[0049] The viscosity of the resin is preferably 50 mPa·s to 5000 mPa·s when mixed with the magnetic powder. If the viscosity is less than 50 mPa·s, the resin will not be entangled with the magnetic powder during mixing, and the magnetic powder and the resin will be easily separated in the container, resulting in deviations in the density or strength of the core. If the viscosity exceeds 5000 mPa·s, the viscosity becomes too high, for example, the formed resin enters the gap between the first magnetic powder, and the second magnetic powder cannot fill the gap, etc., thereby reducing the density of the core and reducing the magnetic permeability.
[0050] SiO2, Al2O3, Fe2O3, BN, AlN, ZnO, TiO2, etc. can be used as viscosity adjusting materials in the resin. The average particle size of the filler used as the viscosity adjusting material can be less than the average particle size of the second magnetic powder, preferably less than 1 / 3 of the average particle size of the second magnetic powder. The reason is that if the average particle size of the filler is large, the density of the obtained core is reduced. In addition, a high thermal conductivity material such as Al2O3, BN, AlN, etc. can be added to the resin.
[0051] The ratio of the apparent density of the core to the true density of the magnetic powder is preferably 76.6% or more and less than 82%. It is more preferably 77% or more. If the ratio is 76.6% or more, the magnetic permeability can be maintained high even in a high magnetic field. On the contrary, if the ratio is less than 76.6%, there is a tendency that the magnetic permeability in a high magnetic field is easily reduced due to the low density. In addition, if the same magnetic permeability characteristics are to be made using a pressed powder core, the ratio of the apparent density of the core to the true density of the magnetic powder will reach about 82% to 88%. The reason is that the pressed powder core is coated with a resin by a powder monomer, and the outer shape is formed at the time of compacting at a very high pressure as described above. In the MC core, the magnetic powder is dispersed and mixed in the resin, and it is only pressurized at a low pressure to the extent that the internal air is discharged as described above, so the resin is not compacted and hardened. Therefore, the ratio of the apparent density of the MC core of this embodiment to the true density of the magnetic powder is less than 82%.
[0052] Furthermore, the surface of the MC core of the present embodiment is different from the surface of the pressed powder core in the following manner. First, as described above, the pressed powder core is manufactured by placing a soft magnetic powder coated with an insulating resin in a metal mold, performing pressure molding at a very high pressure, and subjecting the formed molded body to a heat treatment such as annealing. Therefore, the surface of the pressed powder core is relatively smooth. On the other hand, as described above, the MC core is a composite magnetic powder mixed with an insulating resin placed in a container of a prescribed shape, and molded into a prescribed shape by applying a relatively low pressure. Therefore, the surface of the MC core is rougher than that of the pressed powder core. For example, there are the following differences: the MC core has tiny holes or bumps that are not present in the pressed powder core, and the surface roughness is rougher than that of the pressed powder core.
[0053] In addition, the powder core is formed in the following manner: soft magnetic powder coated with insulating resin is put into the area formed by the inner peripheral surface of the molding hole of the outer mold and the upper surface of the lower mold, and after being compressed by the upper mold, the upper mold is pulled out. At this time, since the soft magnetic powder coated with insulating resin is pressurized at high pressure in the mold, a pressing force is applied to the mold when the formed powder core is taken out. Therefore, sliding marks are formed on the surface of the powder core in the part that slides relative to the inner peripheral surface of the metal mold when it is taken out. The so-called sliding marks refer to multiple linear marks formed by moving while rubbing against the surface of the metal mold. The MC core of this embodiment becomes a core by hardening the resin in the mold, so the core is not pressed by the mold and its surface does not have sliding marks. The surface without sliding marks is a non-sliding surface. All surfaces of the MC core of this embodiment are non-sliding surfaces.
[0054] The coil is a conductive wire with an insulating coating, and copper wire or aluminum wire can be used as the wire material. The coil is formed by winding the conductive wire around at least a portion of the core or is installed and arranged around at least a portion of the core. There is no particular limitation on the winding method of the coil or the shape of the wire material.
[0055] [1-2. Method for manufacturing a reactor]
[0056] Please refer to the attached Figure 1 The method for manufacturing the reactor according to the present embodiment will be described below. Figure 1 As shown, the manufacturing method of the reactor includes: (1) a mixing step, (2) a molding step, (3) a pressurizing step, and (4) a hardening step.
[0057] (1) Mixing process
[0058] The mixing step is a step of mixing the magnetic powder with the resin. The mixing step includes: a magnetic powder mixing step of mixing the first magnetic powder with the second magnetic powder having an average particle diameter smaller than that of the first magnetic powder to form the magnetic powder; and a resin mixing step of adding 3 wt% to 5 wt% of the resin relative to the magnetic powder and mixing the magnetic powder with the resin.
[0059] The mixing in each mixing step can be performed automatically or manually using a predetermined mixer. The mixing time in each mixing step can be appropriately set without particular limitation, and is set to 2 minutes, for example.
[0060] Through this mixing process, a mixture of magnetic powder and resin (hereinafter also referred to as composite magnetic material) can be obtained. Furthermore, the mixing process can also be performed by filling the container for molding the composite magnetic material with magnetic powder and resin and mixing them in the molding process. As a result, there is no need to transfer the composite magnetic material into the container, which can reduce the manufacturing time.
[0061] (2) Molding process
[0062] The molding step is a step of placing the composite magnetic powder in a container of a predetermined shape and molding it into a predetermined shape. In the molding step, a coil may be placed together with the composite magnetic powder and molded.
[0063] As a container, containers of various shapes are used according to the shape of the core to be manufactured. When placing a coil, a box-shaped or dish-shaped container with an open upper surface is used so that the coil can be inserted from above. The container used in the molding process can also be used directly as an outer casing of the reactor that accommodates the core and the coil. If the container is used as the outer casing, there is an advantage that the container does not need to be removed after the composite magnetic powder is hardened. In the case of not using a container as an outer casing, multiple reactors can also be manufactured with one container. That is, multiple recesses can be formed at the bottom of the container, and composite magnetic materials and coils can be placed in the recesses, thereby manufacturing multiple reactors. Therefore, for multiple reactors, only one molding process is required, thereby improving manufacturing efficiency.
[0064] The container used in the molding process may be composed entirely or partially of a resin molded product. By making the container made of resin, the manufacturing cost can be reduced, and the advantage of being able to realize any shape of the MC core can be effectively utilized. That is, since resin is a relatively cheap material, the cost of manufacturing the container can be suppressed, and a core of any shape can be formed by injection molding or the like. As materials for the resin molded product, for example, unsaturated polyester resins, urethane resins, epoxy resins, BMC (bulk molding compound), PPS (polyphenylene sulfide), PBT (polybutylene terephthalate), etc. can be used.
[0065] In addition, the entirety or a portion of the container may be made of a metal having high thermal conductivity, such as aluminum or magnesium, because the composite magnetic material can be easily heated in the pressurizing step as described later.
[0066] (3) Pressurization process
[0067] The pressurizing step is a step of pressing the composite magnetic material with a pressing member during the molding step. By pressing the clay-like composite magnetic material placed in the container with the pressing member, the composite magnetic material is expanded into the shape of the container and the voids contained in the composite magnetic material are reduced, thereby increasing the apparent density.
[0068] When no coil is placed in the container, the composite magnetic material is formed into the shape of the container through the above steps. That is, a molded body of a predetermined shape composed of the composite magnetic material can be obtained.
[0069] In the case of placing a coil in a container, Figure 2As shown, the composite magnetic material 20 is placed in the container 10, and the composite magnetic material 20 is expanded into the shape of the container 10 by the pressing member 30. Thereafter, the coil 40 is inserted into the space formed by pressing the composite magnetic material 20, and the composite magnetic material 20 is filled, and the coil 40 and the composite magnetic material 20 are pressed from above by the pressing member 32. Alternatively, the composite magnetic material 20 may be placed in the container 10, and then the coil 40 (including the inner and outer circumferences thereof) may be buried in the composite magnetic material 20, and the coil 40 and the composite magnetic material 20 may be pressed from above. In this way, by pressing the coil 40 and the composite magnetic material 20 together, the voids contained in the composite magnetic material 20 can be reduced, thereby improving the apparent density and the magnetic permeability. Furthermore, it is also possible to avoid the portion where the coil 40 exists and only press the composite magnetic material 20. In this way, through the above process, a composite magnetic material molded body of a predetermined shape including a coil can be obtained.
[0070] In the pressurizing step, the composite magnetic material may be pressed by a pressing member to form the material into a container shape. In this case, the pressurizing step may be understood as a pressurizing step and a molding step.
[0071] The pressure of pressing the composite magnetic material can be 1.6kg / cm 2 The pressure can be used to increase the apparent density. A more preferred value is 6.3 kg / cm 2 The reason is that if it is less than 6.3kg / cm 2 , the pressing pressure is small, and the effect of increasing the apparent density is small. In addition, even if it is above the above value, it is preferably 15.7kg / cm 2 The reason is that even if the pressure exceeds the above value, the effect of increasing the apparent density is small. In addition, if the pressure exceeds the above value, only the resin is pressed, and the insulation between the magnetic powders deteriorates.
[0072] The time for pressing the composite magnetic material can be appropriately changed according to the content and viscosity of the resin, and can be set to 10 seconds, for example.
[0073] The pressurizing process may also be performed by setting the temperature of the container or the pressing member pressing the composite magnetic material to a temperature higher than normal temperature (for example, 25°C). By increasing the temperature of the container or the pressing member, the resin is heated and becomes soft. Therefore, the composite magnetic material can easily flow into the gap in the container, which can improve the moldability, and the material can easily flow into the voids in the composite magnetic material, which can improve the density. The temperature of the container or the pressing member pressing the composite magnetic material may be higher than the softening point of the resin contained in the composite magnetic material. The reason for this is that the resin can be effectively softened. The pressurizing process may also be performed while maintaining the temperature of the container or the pressing member pressing the composite magnetic material.
[0074] In addition, in the pressurizing step, the composite magnetic material itself may be preheated before pressing the composite magnetic material, in addition to raising the temperature of the container or the pressing member. The composite magnetic material itself may be preheated before pressing while maintaining the temperature of the container or the pressing member pressing the composite magnetic material.
[0075] (4) Hardening process
[0076] The curing step is a step of curing the resin in the molded body obtained in the molding step. When the resin in the molded body is cured by drying, the drying environment can be set to an atmospheric environment. The drying time can be appropriately changed according to the type, content, drying temperature, etc. of the resin, for example, it can be set to 1 hour to 4 hours, but it is not limited to this. The drying temperature can be appropriately changed according to the type, content, drying time, etc. of the resin, for example, it can be set to 85°C to 150°C, but it is not limited to this. Furthermore, the drying temperature is the temperature of the drying environment.
[0077] In addition, the curing of the resin is not limited to drying, and the curing method varies depending on the type of resin. For example, if the resin is a thermosetting resin, the resin is cured by applying heat, and if the resin is an ultraviolet curing resin, the resin is cured by irradiating ultraviolet rays to the molded body.
[0078] The curing step may be repeated for a plurality of times to cure the molded body at a predetermined temperature for a predetermined time. In addition, for example, when the resin is cured by drying, the drying temperature or drying time may be different for each of the plurality of times.
[0079] [1-3. Action and Effect]
[0080] (1) The MC core of this embodiment is a core including magnetic powder and resin. The magnetic powder includes a first magnetic powder and a second magnetic powder having an average particle size smaller than that of the first magnetic powder. The first magnetic powder has a coercive force Hc of 0.70 A / cm or less and a circularity of 0.9 or more.
[0081] Therefore, by using a soft magnetic powder with high circularity and high coercivity for the MC core, a high core density can be achieved, so that the magnetic properties of the MC core can be excellent. In addition, by setting the coercivity of the first magnetic powder to be less than coercivity Hc=0.70 A / cm, the hysteresis loop in the MC core can be reduced, the increase in hysteresis loss can be suppressed, and the reduction in magnetic properties can be suppressed.
[0082] There is also a type of core called a powder core, which is produced by placing soft magnetic powder coated with insulating resin in a metal mold and pressing it at 10 t / cm 2 ~20t / cm 2The powder core is press-formed under high pressure. Compared with the MC core, the powder core is press-formed at 1000 times the high pressure, so it usually has a higher apparent density. In the reactor using a core with a high apparent density, in order to maintain the magnetic permeability in a high magnetic field, a gap is sometimes set between the cores. Although the spacing between the magnetic powders also plays the role of a gap, the powder core has a dense spacing between the magnetic powders and has a weak function as a gap, so it is set as a separation structure to generate a gap. On the other hand, the MC core has sparse spacing between the magnetic powders than the powder core, so the spacing plays the role of a gap, and thus a high magnetic permeability can be obtained in a high magnetic field without a separation structure.
[0083] In addition, as the first magnetic powder, a magnetic powder having a circularity of 0.9 or more and a powder hardness of 278 MPa or more may be used. As such a first magnetic powder, a crushed powder of a Fe-Si-Al alloy powder (send silicon aluminum magnetic alloy) may be cited. By using a soft magnetic powder having a circularity of 0.9 or more and a powder hardness of 278 MPa or more to make an MC core, the apparent density can be set to 89.34 or more. Thus, an MC core having a density and permeability based on the apparent density that are not inferior to those of a pressed powder core can be made.
[0084] (2) Furthermore, the first magnetic powder can be set to have a coercivity of Hc=0.48 A / cm or less and a circularity of 0.92 or more. By setting the circularity to 0.92 or more, a higher core density can be achieved, so that the density and permeability of the MC core can be excellent. In addition, by setting the coercivity to Hc=0.48 A / cm or less, the increase in hysteresis loss can be suppressed, and the reduction in magnetic properties can be suppressed.
[0085] In addition, as the first magnetic powder, a magnetic powder having a circularity of 0.92 or more and a powder hardness of 278 MPa or more may be used. As such a first magnetic powder, gas atomized powder of Fe-Si-Al alloy powder (send silicon aluminum magnetic alloy) and the like may be cited. By using a soft magnetic powder having a circularity of 0.9 or more and a powder hardness of 403 MPa or more to make an MC core, the apparent density may be set to 91.67 or more. Thus, an MC core having a density and permeability based on the apparent density that are comparable to those of a pressed powder core may be made.
[0086] In addition, the core of this embodiment is an MC core, so it has a higher degree of freedom in shape than a powder core, and a core of a desired shape can be easily manufactured even if it is not set as a separate structure. By not setting it as a separate structure, gaps can be eliminated, so when the core of this embodiment is made into a reactor, the leakage flux to the coil can be reduced, and the copper loss can be reduced, thereby suppressing the heating of the coil.
[0087] (3) The magnetic powder includes a first magnetic powder and a second magnetic powder having an average particle size smaller than that of the first magnetic powder, and the amount of the first magnetic powder added relative to the magnetic powder is 60 wt% to 80 wt%, and the amount of the second magnetic powder added relative to the magnetic powder is 40 wt% to 20 wt%. By including the first magnetic powder and the second magnetic powder in the above ratio, the second magnetic powder having a smaller average particle size enters the gaps between the first magnetic powders, thereby achieving an increase in the density of the core and a reduction in iron loss.
[0088] (4) In the core of this embodiment, the resin is 3 wt% to 5 wt% relative to the magnetic powder. This can provide advantages in moldability and can also provide a core with improved productivity and density. That is, since the resin amount is set to 3 wt% to 5 wt%, the composite magnetic material becomes clay-like and is easy to handle, which can improve productivity.
[0089] (5) The entire surface of the core of this embodiment is a non-sliding surface. Therefore, although it is not a powder core, excellent magnetic properties as described above can be obtained. That is, with a powder core, the insulating film covering the magnetic powder will peel off due to sliding marks, so the eddy current loss will deteriorate. On the other hand, the core of this embodiment does not produce sliding marks, so it has low loss compared to the powder core.
[0090] (6) The core manufacturing method of the present embodiment is a core manufacturing method comprising a magnetic powder and a resin, and the magnetic powder comprises a first magnetic powder having a coercive force Hc=0.70A / cm or less and a powder hardness of 278Mpa or more, and a second magnetic powder having an average particle size smaller than that of the first magnetic powder, and the manufacturing method comprises: a mixing step of mixing the magnetic powder with a resin; a molding step of placing the mixture obtained in the mixing step into a prescribed container and molding it; and a hardening step of hardening the resin in the molded body obtained in the molding step.
[0091] Thus, a core with improved density and magnetic permeability can be obtained. Furthermore, by having a pressurizing process, the advantage of the MC core that the shape of the composite magnetic material can be formed into a predetermined shape, i.e., the moldability advantage, can be ensured, and by pressing the composite magnetic material, the material can easily enter the gaps contained in the composite magnetic material, thereby improving the apparent density and magnetic properties of the core.
[0092] [1-4. Example]
[0093] Refer to Tables 1 to 4 and Figure 3 Embodiments of the present invention will be described.
[0094] (Measurement Items)
[0095] The measurement items are density, magnetic permeability and iron loss Pcv. For each core sample produced, 40 turns of winding are performed using a φ2.6mm copper wire to produce a reactor. The shape of each core sample is set to a ring shape with an outer diameter of 35mm, an inner diameter of 20mm, and a height of 11mm. In addition, the magnetic permeability and iron loss Pcv of the produced reactor are calculated under the following conditions.
[0096] <Density>
[0097] The density of the core is the apparent density. That is, the outer diameter, inner diameter, and height of each core sample are measured, and based on these values and π×(outer diameter 2 -Inner diameter 2 )×height to calculate the volume of the sample (cm 3 ). Then, the mass of the sample is measured, and the density of the core is calculated by dividing the measured mass by the calculated volume.
[0098] <Magnetic Permeability and Iron Loss>
[0099] The measurement conditions of magnetic permeability and iron loss Pcv are set to a frequency of 20kHz and a maximum magnetic flux density of Bm = 30mT. The magnetic permeability is the amplitude permeability when the maximum magnetic flux density Bm is set when measuring the iron loss Pcv. The iron loss Pcv is calculated using a BH analyzer (Yantong Measurement Co., Ltd.: SY-8219) as a magnetic measurement device. The calculation is performed by using the following formulas (1) to (3) and using the least squares method to calculate the hysteresis loss coefficient and eddy current loss coefficient for the frequency curve of the iron loss Pcv.
[0100] Pcv=Kh×f+Ke×f 2 …(1)
[0101] Phv=Kh×f…(2)
[0102] Pev=Ke×f 2 …(3)
[0103] Pcv: Iron loss
[0104] Kh: Hysteresis loss coefficient
[0105] Ke: Eddy current loss coefficient
[0106] f: frequency
[0107] Phv: Hysteresis loss
[0108] Pev: Eddy current loss
[0109] In this example, the average particle size and circularity of each powder were obtained by taking the average value of 3000 particles using the following apparatus: the powder was dispersed on a glass substrate, a photograph of the powder was taken using a microscope, and each particle was automatically measured based on the image.
[0110] Company name: Malvern
[0111] Device name: Morphologi G3S
[0112] The specific surface area is measured by the Brunauer Emmitt Teller (BET) method.
[0113] [1. First property comparison (comparison based on the type of soft magnetic powder)]
[0114] In the first property comparison, the properties are compared by changing the types of the first magnetic powder and the second magnetic powder contained in the soft magnetic powder.
[0115] (Sample preparation method)
[0116] In this property comparison, the types of the first magnetic powder and the second magnetic powder were changed to produce cores of Examples 1 to 5 and Comparative Example 1. In producing the cores, the powders listed in Table 1 were used as the first magnetic powder, and the powders listed in Table 2 were used as the second magnetic powder.
[0117] [Table 1]
[0118]
[0119] [Table 2]
[0120]
[0121] Hereinafter, a method for producing a core sample will be described in the following procedure.
[0122] The core samples of Examples 1 to 5 and Comparative Example 1 were produced according to the combination of the first magnetic powder and the second magnetic powder, the ratio of the magnetic powder added, the amount of epoxy resin added, and the pressing pressure shown in Table 3.
[0123] [Table 3]
[0124]
[0125] (Production order)
[0126] As a mixing process, the first magnetic powder and the second magnetic powder of the type corresponding to Examples 1 to 5 and Comparative Example 1 were mixed in a V-type mixer at a weight ratio of 70:30 for 30 minutes to form a magnetic powder. Furthermore, the magnetic powder was placed in an aluminum cup, 4.0 wt% of epoxy resin was added to the magnetic powder, and the mixture was manually mixed for 2 minutes using a spatula. Thus, a composite magnetic material as a mixture of the magnetic powder and the resin was obtained.
[0127] Next, the composite magnetic material obtained in the mixing step was filled into a resin container having a doughnut-shaped space and was pressed at 6.3 kg / cm using a hydraulic press. 3 The composite magnetic material in the container was pressed for 10 seconds at a pressing pressure of 10° C. to produce a ring-shaped molded body. During the pressing period, the temperature of the container was maintained at 25° C.
[0128] The molded body obtained in the pressurizing step and the molding step was dried in the air at 85° C. for 2 hours, then dried at 120° C. for 1 hour, and further dried at 150° C. for 4 hours to prepare a toroidal core as a sample.
[0129] [Table 4]
[0130]
[0131] Table 4 shows the apparent density, initial magnetic permeability μ0, magnetic permeability μ0 of the MC cores of Examples 1 to 5 and Comparative Example 1. 12k , iron loss Pcv (iron loss Pcv, hysteresis loss Phv, eddy current loss Pev). The magnetic permeability in Table 4 is the amplitude magnetic permeability, which is calculated by using the impedance analyzer and based on the inductance value of each magnetic field strength at 20kHz and 1.0V. The "μ0" in Table 4 represents the initial magnetic permeability when there is no superimposed DC, that is, the magnetic field strength is 0H (A / m). The "μ0" in Table 4 represents the initial magnetic permeability when the DC is not superimposed, that is, the magnetic field strength is 0H (A / m). 12k ” indicates the magnetic permeability when the magnetic field strength is 12kH (kA / m).
[0132] Based on Table 4 Figure 3 of charts. Figure 3 It is the magnetic permeability μ relative to the iron loss Pcv 12k of charts.
[0133] (Correlation between the coercive force and powder hardness of the first magnetic powder and the magnetic properties of the MC core)
[0134] As shown in Table 4 and Figure 3As shown in Table 4, in Comparative Example 1 using the first magnetic powder with a coercive force of 1.83 A / cm, the iron loss Pcv of the MC core is 22.9. In contrast, in the MC cores of Examples 1 to 5 using the first magnetic powder with a coercive force Hc=0.70 A / cm or less, the iron loss Pcv is 16.7 or less. The reason is that if the coercive force of the first magnetic powder is 1.83 A / cm or more, the hysteresis loss Phv increases due to the influence of the coercive force. In addition, according to Table 4, in Comparative Example 1, not only the hysteresis loss Phv increases, but also the eddy current loss Pev increases, and both the hysteresis loss and the current loss Pev increase, thereby increasing the iron loss Pcv.
[0135] As described above, the circularity of the first magnetic powder has an effect on the magnetic permeability (μ 12k ) has a great influence. As shown in Table 4, in Example 2 using the first magnetic powder with a circularity of 0.90, the magnetic permeability (μ 12k ) is also 15.2. This value is a sufficiently high magnetic permeability. Furthermore, in Example 1, Example 3 to Example 5, in which the circularity is set to 0.92 or more, the magnetic permeability (μ 12k ) is 20.3 or more. Since the circularity is different by 0.02, the magnetic permeability (μ 12k ) differ by more than 5. On the other hand, in Example 1 (circularity 0.92) and Example 3 (circularity 0.94) whose circularity differs by 0.02, the magnetic permeability (μ 12k ) is 0.02. That is, in order to increase the magnetic permeability (μ 12k ), the circularity of the first magnetic powder can be set to 0.90 or more, and the magnetic permeability (μ 12k ).
[0136] Based on the above, as shown in Example 2, by using the first magnetic powder having a coercive force of 0.70 A / cm or less and a circularity of 0.90 or more, it is possible to achieve both excellent magnetic permeability (μ 12k ) and a MC core with low iron loss. Furthermore, as shown in Examples 1 and 3 to 5, by setting the coercivity of the first magnetic powder to 0.48 A / cm or less and the circularity to 0.92 or more, it is possible to achieve both excellent permeability (μ 12k ) and low iron loss and also achieves a better overlap permeability (μ 12k )'s MC core.
[0137] (Correlation between the coercive force and powder hardness of the second magnetic powder and the magnetic properties of the MC core)
[0138] As shown in Table 3, in the combination of Example 1 and Example 5, and the combination of Example 3 and Example 4, the type of the first magnetic powder is the same in each group, but the type of the second magnetic powder is different. The coercive force of the second magnetic powder used in Example 4 and Example 5 is Hc=0.61 A / cm or less, and the coercive force of the second magnetic powder used in Example 1 and Example 3 is Hc=0.93 A / cm or less. It is found that even when a magnetic powder having a coercive force of Hc=0.93 A / cm or less is used as the second magnetic powder, the iron loss Pcv can be set to 16.7 or less.
[0139] That is, as shown in Examples 1 and 3, by setting the coercivity of the second magnetic powder used in the MC core to Hc=0.93 A / cm or less and the circularity to 0.98 or more, it is possible to achieve both excellent permeability (μ 12k ) and a MC core with low iron loss. Furthermore, as shown in Examples 4 and 5, by setting the coercivity of the second magnetic powder to 0.61 A / cm or less, the hysteresis loss can be further reduced, and an excellent permeability (μ 12k ), and can realize MC core with lower iron loss.
[0140] [2. Second property comparison (density ratio between the apparent density of the MC core and the apparent density of the powder core)]
[0141] This property comparison uses the same type of magnetic powder as the first magnetic powder used in Example 4, Example 5, and Comparative Example 1, and produces a pressed powder core based on conditions such that the apparent density becomes high, and compares the apparent density of the produced pressed powder core with that of the MC core of Comparative Example 1, Example 4, and Example 5.
[0142] When comparing the apparent density of the MC core with the apparent density of the pressed powder core, the conditions of the magnetic powder of the pressed powder core to be compared with the MC core are partially changed from the first magnetic powder used in Example 4, Example 5, and Comparative Example 1. That is, instead of simply using the first magnetic powder having the same average particle diameter as the first magnetic powder used in Example 4, Example 5, and Comparative Example 1, the average particle diameter of the first magnetic powder is set to obtain a pressed powder core having the optimal apparent density. In addition, the presence or absence of the addition of the second magnetic powder is also an important factor in the production conditions of the pressed powder core having the optimal apparent density, so from the viewpoint of producing the pressed powder core having the optimal apparent density, it is appropriate to determine the presence or absence of the addition of the second magnetic powder.
[0143] The powder cores used as comparison objects of Comparative Example 1, Example 4, and Example 5 were produced under the following conditions.
[0144] ·Method for manufacturing a powder core used as a comparison object of Comparative Example 1
[0145] (1) 0.5 wt% of alumina powder was mixed with Fe-6.5Si alloy powder having an average particle size (D50) of 35 μm produced by gas atomization.
[0146] (2) 0.5 wt % of silicone oligomer was added to Fe-6.5Si alloy powder mixed with alumina powder, and the mixture was heated and dried at 200° C. for 2 hours.
[0147] (3) 1.5 wt % of silicone resin was mixed with the dried powder, and the mixture was heated and dried at 150° C. for 2 hours.
[0148] (4) Screening with a mesh size of 250 μm was performed to break up the lumps generated after heat drying. Thereafter, 0.5 wt % of ethylene bisstearyl amide was mixed as a lubricant.
[0149] (5) Forming pressure 15 ton / cm 2 The Fe-6.5Si alloy powder having the insulating film formed thereon through the above steps is produced into a compact.
[0150] (6) Finally, the compact was heat treated at 850°C in a nitrogen atmosphere for 2 hours to produce a powder magnetic core.
[0151] ·Method for manufacturing a powder core used as a comparison object of Example 4
[0152] (1) A first amorphous powder having an average particle size (D50) of 35 μm prepared by water gas atomization and a second amorphous powder having an average particle size (D50) of 5.0 μm prepared by water atomization were mixed at a ratio of 70:30. 1.3 wt% of low melting point glass and 0.3 wt% of lithium stearate as a lubricant were added to the mixed powders. The mixing was performed using a V-type mixer for 1 hour.
[0153] (2) 0.1 wt % of a silane coupling agent and 1.5 wt % of a silicone resin were mixed with the mixed powder, and the mixture was heated and dried at 150° C. for 2 hours.
[0154] (3) Screening with a mesh size of 250 μm was performed to break up the lumps generated after heat drying. Thereafter, 0.3 wt % of lithium stearate was mixed as a lubricant.
[0155] (4) Forming pressure 15 ton / cm 2 The mixed powder having the insulating film formed thereon through the above steps is produced into a compact.
[0156] (5) Finally, the compact was heat treated at 420° C. in the atmosphere for 2 hours to produce a powder magnetic core.
[0157] ·Method for manufacturing a powder core used as a comparison object of Example 5
[0158] (1) 0.3 wt % of a silane coupling agent and 1.0 wt % of a silicone oligomer were added to Fe-Si-Al alloy powder having an average particle size (D50) of 35 μm prepared by gas atomization, mixed, and heated and dried at 200° C. for 2 hours.
[0159] (2) 1.5 wt % of a silicone resin was mixed with the dried powder, and the mixture was further heated and dried at 150° C. for 2 hours.
[0160] (3) Screening with a mesh size of 250 μm was performed for the purpose of breaking up the lumps generated after heat drying. Thereafter, 0.5 wt % of ethylene bisstearyl amide was mixed as a lubricant.
[0161] (4) Forming pressure 15 ton / cm 2 The Fe—Si—Al alloy powder having the insulating film formed thereon through the above steps is produced into a compact.
[0162] (5) Finally, the compact was heat treated at a heat treatment temperature of 700° C. in the atmosphere for 2 hours to produce a powder magnetic core.
[0163] [Table 5]
[0164]
[0165] Table 5 shows the apparent density and density ratio (apparent density / theoretical density) of the MC cores of Comparative Example 1, Example 4, and Example 5, and the ratio of the apparent density of the MC core to the apparent density of the powder core used as the comparison object of Comparative Example 1, Example 4, and Example 5. Figure 4 of charts. Figure 4 This is a graph showing the ratio of the apparent density of the MC core to the apparent density of the powder core with respect to the first powder hardness.
[0166] As shown in Table 5, the apparent density of the MC core of Comparative Example 1 with a powder hardness of 255 MPa is 5.91 g / cm 3 The apparent density of the powder core used as the comparison object of Comparative Example 1 is 6.65 g / cm 3. Based on these values, in Comparative Example 1, if the ratio of the apparent density of the MC core to the apparent density of the pressed powder core is calculated, it is 88.87% (5.91÷6.65×100). Similarly, in Example 4 with a powder hardness of 700 MPa, the ratio of the apparent density of the MC core to the apparent density of the pressed powder core is 91.67%, and in Example 5 with a powder hardness of 403 MPa, the ratio of the apparent density of the MC core to the apparent density of the pressed powder core is 89.34%.
[0167] like Figure 4 As shown, there is a correlation between the powder hardness of the first magnetic powder and the ratio of the apparent density of the MC core to the apparent density of the pressed powder core. If the powder hardness of the first magnetic powder is increased, the ratio of the apparent density of the MC core to the apparent density of the pressed powder core increases. That is, if the powder hardness is increased, the apparent density of the MC core approaches the apparent density of the pressed powder core produced under the condition that the apparent density becomes high. This is particularly significant when the powder hardness is 403 MPa or more. Based on the above, by using the first magnetic powder with a powder hardness of 403 MPa or more, the apparent density of the MC core can be made close to the apparent density of the pressed powder core.
[0168] [3. Other embodiments]
[0169] The present invention is not directly limited to the embodiments, and the constituent elements may be deformed and embodied in the implementation stage without departing from the scope of the main purpose. In addition, various inventions may be formed by using appropriate combinations of multiple constituent elements disclosed in the embodiments. For example, some constituent elements may be deleted from all constituent elements shown in the embodiments. Furthermore, constituent elements in different embodiments may also be appropriately combined.
[0170] In the present invention, the MC core manufacturing process includes a pressurizing process, but it can be omitted. The MC core can also be manufactured through a mixing process, a molding process, and a curing process according to the density, magnetic permeability, or iron loss Pcv that the MC core is intended to achieve.
Claims
1. A method for manufacturing a metal composite core, which is a method for manufacturing a core comprising magnetic powder and resin, characterized in that: The magnetic powder includes a first magnetic powder having a coercive force Hc of 0.70 A / cm or less, a circularity of 0.9 or more, and a powder hardness of 278 MPa or more, and a second magnetic powder having an average particle diameter smaller than that of the first magnetic powder, a coercive force Hc of 0.93 A / cm or less, a circularity of 0.98 or more, and a powder hardness of 239 MPa or more, and the manufacturing method includes: A mixing step of mixing the magnetic powder with a resin; a molding step of placing the mixture obtained in the mixing step into a predetermined container and molding it; and The curing step is to cure the resin in the molded body without applying pressure to the molded body obtained in the molding step.
Citation Information
Patent Citations
Manufacturing method of magnetic element and magnetic element
JP2012033727A
Soft magnetic powder, core, and method for manufacturing the same
JP2015032708A
Method for manufacturing reactor and method for manufacturing core, and core and reactor
JP2018098259A